"I like it, but I don't use it": Impact of carsharing business models on usage intentions in the sharing economy. (30th December 2019) - Hahn, Rüdiger; Ostertag, Felix; Lehr, Adrian; Büttgen, Marion; Benoit, Sabine
Abstract: Carsharing is often promoted as a potentially environmental‐friendly alternative to individual car ownership. However, various carsharing programs have displayed limited success in the past. An initial field study of a new carsharing service is such a story of failure: The introduction of this new service at a medium‐sized German university generated unexpectedly low adoption rates so that the service was eventually scaled down and then suspended. Quantitative field study results as well as additional qualitative focus groups reveal that missing compatibility is a key barrier to adoption. Drawing on extant conceptual frameworks of user participation in sharing business models, a factorial survey identifies the importance of different dimensions of carsharing business models for their acceptance. The results reveal that a set of convenience and lifestyle dimensions influences usage intentions, including mode of drive, pickup and drop‐off mode, service level, price model, availability, and type of market mediation. In contrast, vehicle fleet does not appear to influence carsharing models' acceptance. These findings contribute to research on business model configuration as well as the attitude–behavior gap in the sharing economy by determining relevant dimensions of a carsharing business model that can bridge the gap between basically positive attitudes and usage resistance. Thereby, they also serve for concrete managerial recommendations.